Renal transplantation experience in Cairo University hospitals - Mohammed G Saadi; Sahier O El-Khashab; Rabab M.A. Mahmoud (SpringerOpen, 2016)
Background Worldwide, the population treated with renal replacement therapy is increasing, representing ∼1.3 million patients who undergo dialysis and 400 000 patients who are alive with a kidney transplant. Transplantation is more predictable than it was 20-30 years ago and innovation over the last 20 years has been rapid, delivering substantial short-term and medium-term improvements. Many reports have been published about the epidemiology of renal transplantation in different countries. The aim of this study was to identify the epidemiology of renal transplantation in Cairo University hospitals. Patients and methods This is a retrospective study that was conducted at the King Fahd Unit, Faculty of Medicine, Cairo University, on 282 patients. All patients were followed up for a period of at least 1 year. Demographic data, history taking, clinical examination, immunosuppressive medications protocol, and laboratory investigations were recorded for every patient. Results Of the 282 patients included in the study, 68.1% of recipients were male and 31.9% were female, whereas 52.5% of donors were male and 47.5% were female. An overall 98.6% of our patients received living kidney transplants, whereas 1.4% received cadaveric kidney transplants. The most common cause of end-stage renal disease was unknown etiology. The mean BMI increased significantly after transplantation to reach 22.6±4.0 (P=0.0001). Hypertension was the most common disease among the patients; 82.2% of our patients were already hypertensive before transplantation. Conclusion The majority of our recipients were male patients in their second and third decades of life, Moreover, the majority of donors were also male individuals in their second and third decades of life. Most of the transplants carried out by us are living-donor procedures.